Algorithm for Calculating the Parameters of a Garden Boom Sprayer for Pesticide Application - I. G. Smirnov; G. I. Lichman; L. A. Marchenko (Сельскохозяйственные машины и технологии, 2022)
It is noted that for the rational use of pesticides in industrial horticulture, it is necessary to reduce their consumption practicing the local treatment of each plant, uniform distribution of the working fluid at a set rate while treating a tree’s or a shrub’s crown. The analysis of the technical equipment of modern industrial horticulture in Russia reveals an insufficient level of mechanization in terms of managing the parameters of both the technological process and machinery. (Research purpose) To develop an algorithm for calculating the parameters of a boom garden sprayer when treating fruit plants with pesticides, to ensure their high-quality application, reduce losses and eliminate the risks of environmental pollution. (Materials and methods) The research is based on analytical methods of optimization offered by applied mathematics, the theory of choosing the parameters of agricultural mobile machines, criteria for assessing the quality of the working fluid distribution during the fruit plant treatment, data on the crown shape of the trees and shrubs being cultivated. (Results and discussion) It was established that the amount of working fluid per unit length of the perimeter and the quality of distribution depend on the shape of the spray jet distribution diagram, the degree of the distribution diagrams overlap, the distance between the boom and the tree’s or shrub’s axis of symmetry, the distance of the nozzles from the boom, the shape of the distribution diagram. Analytical dependencies were obtained to calculate the rate (dose) of pesticides and the quality of their distribution over the treated surface. (Conclusions) An algorithm for the analytical calculation of a boom garden sprayer parameters was developed, which makes it possible to evaluate the impact on the rate of applying pesticides and on the quality of distributing the pesticide working liquid, characterized by the variation coefficient. At the same time, the following parameters were taken into account: the distribution diagram of the pesticide working fluid, the number of nozzles on the vertical sprayer boom, the height of their location on the boom, the distance from the boom to the crown surface, the distance between the boom and the trunk of the tree treated, the crown perimeter. The algorithm was verified for specific parameter values: the distance of 1.0 meter from the vertical boom to the axis of the tree (shrub) trunk; the distance of 0.5 meter between the nozzles and the vertical bar, the height of the nozzles on the vertical bar of 0.3, 0.8 and 1.3 meter, the working fluid flow rate of 2.5 liters per minute, the coefficient characterizing the distribution diagram of 5.61. The dose of the pesticide working solution to apply was calculated as follows: 174.6 liters per hectare with a coefficient of variation of 4.94 percent, which corresponds to the agrotechnical requirements.